Role of connexins in infantile hemangiomas - Blanke, Katja; Dähnert, Ingo; Salameh, Aida (Frontiers in Pharmacology, 2013)
The circulatory system is one of the first systems that develops during embryogenesis. Angiogenesis describes the formation of blood vessels as a part of the circulatory system and is essential for organ growth in embryogenesis as well as repair in adulthood. A dysregulation of vessel growth contributes to the pathogenesis of many disorders. Thus, an imbalance between pro- and antiangiogenic factors could be observed in infantile hemangioma (IH). Infantile hemangioma is the most common benign tumor during infancy, which appears during the first month of life. These vascular tumors are characterized by rapid proliferation and subsequently slower involution. Most IHs regress spontaneously, but in some cases they cause disfigurement and systemic complications, which requires immediate treatment. Recently, a therapeutic effect of propranolol on IH has been demonstrated. Hence, this nonselective β- blocker became the first-line therapy for IH. Over the last years, our understanding of the underlying mechanisms of IH has been improved and possible mechanisms of action of propranolol in IH have postulated. Previous studies revealed that gap junction proteins, the connexins (Cx), might also play a role in the pathogenesis of IH. Therefore, affecting gap junctional intercellular communication is suggested as a novel therapeutic target of propranolol in IH. In this review we summarize the current knowledge of the molecular processes leading to IH and provide new insights of how connexins might be involved in the development of these vascular tumors.